'Saying it without saying it': using poetry as a way to talk about important issues in nursing practice. (November 2017) - Jack, Kirsten; Illingworth, Sam
The aim of this study was to explore the ways in which student nurses use self-authored poems to think about important aspects of nursing practice. Being a nurse can be rewarding in that it affords opportunities to care for and communicate with others. However, it can also yield challenges, and nurses are often faced with practice filled with uncertainty, grief and loss. Our findings suggest that students can use poetry writing to meaningfully explore nursing practice, engage with critical thinking and consider the feelings of others. Of particular note were the ways in which students use metaphor to explore emotional and relational aspects of practice and the technique of self-distancing when describing difficult and angering events. The work has implications for nurse education and practice. Proactively encouraging students to adopt particular ways of expressive writing might be beneficial for student health and wellbeing. Such an approach has the potential to improve quality care provision and support the emotional health of student nurses, which might lead to a reduction in compassion fatigue, stress and attrition.